Inferior vena cava to aorta ratio in dehydrated pediatric patients: a systematic review and meta-analysis - Gilbert Sterling Octavius; Michelle Imanuelly; Johan Wibowo; Nadia Khoirunnisa Heryadi; Melanie Widjaja (The Korean Pediatric Society, 2023)
Background Dehydration due to acute diarrhea is among the leading causes of mortality. However, advancements in management and technology do not help clinicians differentiate dehydration degrees. Ultrasound using the inferior vena cava to aorta (IVC/ Ao) ratio is a promising noninvasive technique to identify significant pediatric dehydration. Puspose Therefore, this systematic review and meta-analysis aimed to examine the diagnostic parameters of the IVC/Ao ratio for predicting clinically significant dehydration in pediatric patients. Methods We searched the MEDLINE, PubMed, Cochrane Library, ScienceDirect, and Google Scholar databases for studies of pediatric patients (≤18 years old) who presented with signs and symptoms of dehydration due to acute diarrhea, gastroenteritis, or vomiting. The inclusion criteria were cross-sectional, case-control, cohort, and randomized controlled trial study design and publication in any language. We then conducted a meta-analysis using the midas and metandi commands from Stata software. Results Five studies of 461 patients were included. The combined sensitivity was 86% (95% confidence interval [CI], 79%-91%), while the specificity was 73% (95% CI, 59%-84%). The area under the curve was 0.89 (95% CI, 0.86-0.91). The positive likelihood ratio (LR+) was 3.2 (95% CI, 2.1-5.1) with a 76% posttest probability, while the negative likelihood ratio (LR-) was 0.18 (95% CI, 0.12-0.28) with a 16% posttest probability. The combined negative predictive value was 0.83 (95% CI, 0.75-0.91), while the positive predictive value was 0.75 (95% CI, 0.68-0.82). Conclusion The IVC/Ao ratio was insufficient to exclude or confirm significant dehydration in pediatric patients. More studies are needed, especially multicenter, adequately powered diagnostic research, to will help establish the usefulness of the IVC/Ao ratio